2017
DOI: 10.1016/j.jgeb.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of deoxyribonuclease from small intestine of camel Camelus dromedarius

Abstract: The chromatography of deoxyribonuclease (DNase) from small intestine of camel Camelus dromedarius by DEAE-Sepharose separated three isoforms DNase 1, DNase 2 and DNase 3. The DNase 3 was purified to homogeneity by chromatography on Sephacryl S-200. The molecular weight of DNase 3 was 30 kDa using gel filtration and SDS-PAGE. The pH optimum of DNase 3 was reported at 7.0 using Tris-HCl buffer. The temperature optimum of DNase 3 was found to be 50 °C. The enzyme was stable up to 50 °C for one h incubation. The K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Both enzymes are proved to be stable up to 50 °C. 23 , 24 Further sonication was performed by a probe-type sonicator at 35 W for 30 min to produce the final product. The scheme of the liposome preparation procedures is illustrated in Suppl.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both enzymes are proved to be stable up to 50 °C. 23 , 24 Further sonication was performed by a probe-type sonicator at 35 W for 30 min to produce the final product. The scheme of the liposome preparation procedures is illustrated in Suppl.…”
Section: Methodsmentioning
confidence: 99%
“…Hematoxylin and eosin (H&E) staining was performed for a histological examination of the skin under optical microscopy, as described previously. 24 …”
Section: Methodsmentioning
confidence: 99%
“…While we used abiotic environmental factors to quantify and predict eoDNA degradation, the actual degradation is most likely biotic, caused by free DNAses and microbes in the feces (Dash & Das, 2018; Regnaut et al, 2005). Free DNAses profit from water availability under high humidity and speed up enzymatic processes under higher temperature (Abdel‐Gany et al, 2017). Better growth of DNA‐degrading microbes at higher temperatures (Eichmiller et al, 2016) further expedites DNA degradation, for example, in feces (Murphy et al, 2007; Nsubuga et al, 2004), feathers (Vili et al, 2013), and hair (Sawaya et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that DNA obtained from mice samples presented a smear whereas samples in vitro contained a single DNA band. The smear from caecum and colon samples could be derived from DNAses present in the intestinal lumen that could degrade the DNA 201 . We speculated that these unspecific fragments of different sizes could be affecting to the entire protocol, because after DNA fragmentation, adaptors will be added to these unspecific fragments.…”
Section: Transposition Mutagenesis Sequencing and Analysismentioning
confidence: 99%